Towards Firm Value Based on Capital Structure - Rustam HANAFI; Luluk Muhimatul IFADA; Muohamad Chilmi FAJRI (Communications of International Proceedings, 2021)
The determinants of firm value in this study are the influence of profitability, liquidity, dividend policy through the capital structure as a mediating variable. This research was conducted on the Indonesia Stock Exchange using the company analysis unit in the Jakarta Islamic Index. This study used the purposive sampling method, which amounted to 56 companies with the research period in 2016-2019. This type of research is quantitative research. The results of this study indicate that profitability has a positive effect on capital structure and firm value. Meanwhile, liquidity has a negative effect on capital structure but has no significant positive effect on firm value. Furthermore, dividend policy has a positive effect on firm value. This study found that capital structure has a significant positive effect on firm value, but the capital structure cannot mediate the relationship between profitability and liquidity on firm value.
Keywords: profitability; liquidity; dividend policy; capital structure; firm value.